Community Service Activities: Discover the Unique Selling Proposition of Fermented Cassava from Different Packaging - Haryanto, Lorenta In; Rahmadona, Lola; Putri, Dessy Iriani; Sukrianto; Tanjung, Dian Diani (International Journal of Community Service Learning, 2023)
Waru Village has excellent business prospects for Fermented Cassava as a home industry product. The existing problems encountered by the producer were limited product shelf life, the absence of a unique selling proposition, and the lack of brand identity. This community service activity aimed to educate the importance of good packaging and provide training on the production and packaging of Fermented Cassava with various forms of material. It was conducted in March 2022, in Waru Village, Parung Sub-district, using two methods, i.e seminar and demonstration method. The type and research approach used was descriptive analysis with a qualitative approach. Data collection techniques were obtained from observation, interviews, and documentation. The technique applied to measure the profitability index and partners' perceptions was the R/C ratio and Likert scale. The R/C ratio is 1,37, while the simulation demonstrated that producers could increase profits by up to 375% and 416% by repackaging the product with bamboo buckets and plastic boxes. This study concludes that the production of Fermented Cassava is profitable and partners are aware of the product's unique selling propositions.